The Value of Skills - Francis Green (University of Kent, Department of Economics, 1998)
Many commentators have argued that "key skills" are becoming more important in modern workplaces. This paper draws on a survey that uses a methodology based on job analysis to measure skills at work, and estimates their implicit prices using a hedonic wage equation. The main new findings are that: (a) Computer skills are highly valued in the current British labour market. Even at "moderate" levels of complexity, for example using word-processing packages, workers using computers earn an average premium (after controlling for other job skills) in excess of 20 per cent, compared to those who do not use computers at all. (b) Professional communication and problem-solving skills are also highly valued. A one-standard-deviation increase in either type of skill raises pay by around 5 per cent, after allowing for all the controls. To a lesser extent, verbal skills also carry a pay premium for women. But planning, and client and horizontal communication skills, have little independent association with pay. Numerical skills also have no conditional link with pay, other than through being associated with more complex computer usage. (c) Jobs involving task variety earn more pay, but there is no strong evidence that greater autonomy is positively rewarded. (d) Participating in Quality Circles and, more tentatively, in organised work teams attracts a pay premium. (e) Jobs which require a long learning time, which deploy transferable skills, and/or for which there are higher qualifications requirements command a higher pay. (f) A reasonably complete job analysis provides a useful means of accounting for a wage distribution via a hedonic wage equation.
Keywords: J31; 330; Skills; Wages; Computers; Berufsbildung; Qualifikation; Lohn; Schätzung; Großbritannien